Estimation of some qualitative traits in dry seed pea (Pisum sativum) varieties compare to local wild variety in Sulaimani region: Key word: A comparative study, Pea varieties, Chemical components, Chemical elements, Correlation. - Abdolla, Bestoon Ali; Tofiq, Sherwan Ismail (Journal of Kerbala for Agricultural Sciences, 2019)
The present study was conducted in the Sulaimani region during 2019to estimate some chemical components of five peas varieties (American,Avola, pakland, Jeza and Local wild Sulaimani) according to a completely randomized design CRD, replicated three times. Means comparison was carried out using the least significant difference test (LSD) at 0.01 significant levels. The results of this study summarized as follow: There were highly significant differences among varieties for all chemical components, exception of P%, which was only significant. The Jeza variety produced the highest percentage of fiber, oil, and moisture reached 4.27, 3.13, and 11.71% respectively, while the Pakland variety showed the highest percentage of K and Mg reached 1.22 and 0.15%, respectively. The highest value of most chemical components, including protein, ash, starch, total N, Ca, and P% produced by local wild Sul. variety reached 26.63, 6.83, 42.71, 4.27, 0.31 and 0.15%, respectively . The protein % correlated high significantly and positively with ash, starch and P% (r = 0.927, 0.958 and 0.789, p < 0.01) respectively, while it correlated high significantly and negatively with fiber% (r =- 0.813, p < 0.01), and also there are significant and negative correlation between protein and moisture (r = - 0.745, p < 0.01)